Method for preparing eutecticevaporate gel by utilizing pretreatment separation liquid and application of eutecticevaporate gel

By preparing a eutectic gel with synergistic effects of lignin, hemicellulose, and copper ions, the problems of resource utilization of separation liquid and single function of gel material are solved, achieving multifunctionality and stability, and making it suitable for flexible strain sensors and catalytic degradation of organic pollutants.

CN120865575APending Publication Date: 2025-10-31ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510919128.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In the existing technology, there is no effective way to utilize the separation liquid generated after biomass pretreatment with eutectic solvents, which leads to resource waste and environmental pollution. At the same time, traditional gel materials have limited functions and cannot meet the requirements for mechanical strength, environmental stability and catalytic activity.

Method used

Moso bamboo was pretreated with an alkaline eutectic solvent of urea/monoethanolamine. The separated liquid was collected and reacted with acrylamide monomer, crosslinking agent and initiator to form a eutectic gel. The gel was then impregnated with CuCl solution for adsorption, thus constructing a multifunctional gel with synergistic effects of lignin, hemicellulose and copper ions.

Benefits of technology

It achieves the multifunctionality of eutectic gel, possesses conductivity and catalytic activity over a high strain range, can remain stable in extreme environments, and provides flexible strain sensors and efficient catalytic degradation capabilities for organic pollutants.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing eutecticevaporate gel by utilizing a pretreatment separation liquid and application, and belongs to the technical field of biomass resource utilization and functional materials. The method comprises the following steps: pretreating moso bamboos with a urea / monoethanolamine alkaline eutectic solvent (ADES), and collecting a separation liquid; mixing the separation liquid, acrylamide, a cross-linking agent and an initiator for reaction to form eutectic gel (DES gel); and dipping the gel in a CuCl solution to adsorb Cu2. The obtained eutecticevaporate gel has excellent mechanical properties, freezing resistance and ultraviolet resistance, the conductivity is remarkably improved after Cu2 is adsorbed, and the eutecticevaporate gel is suitable for constructing a flexible strain sensor which is high in linearity, wide in strain range and stable at low temperature and can also be used for efficient catalytic degradation of organic pollutants. All-component high-value utilization of the biomass pretreatment separation liquid is achieved, the raw material cost is low, and the green manufacturing concept is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomass resource utilization and functional materials technology, specifically to a method and application for preparing eutectic gels using a pretreated separation liquid. Background Technology

[0002] The efficient utilization of lignocellulosic biomass faces two major challenges: First, traditional pretreatment methods (such as acid / alkali methods) produce waste liquids containing large amounts of lignin and hemicellulose, leading to resource waste and environmental pollution when directly discharged. Second, existing gel materials have limited functionality, making it difficult to simultaneously meet the requirements for mechanical strength, environmental stability, and catalytic activity. Although eutectic solvent (DES) pretreatment can efficiently separate biomass components, there is still a lack of effective pathways for the direct resource utilization of the separated liquid. Currently, while DES pretreatment can efficiently separate biomass components, the direct and high-value resource utilization of the separated liquid (rich in lignin, hemicellulose, and residual DES) generated during pretreatment still lacks effective pathways and is often treated as waste, resulting in resource waste and potential environmental risks. Traditional gel materials have limited functionality, making it difficult to simultaneously meet the requirements for mechanical strength, environmental stability, conductivity, and catalytic activity, and they often rely on synthetic polymers or noble metal loadings, resulting in high costs and poor biocompatibility. Therefore, developing a method to directly and efficiently utilize pretreated separated liquids to prepare multifunctional eutectic gels and expanding their applications in flexible electronics, environmental catalysis, and other fields is of great significance. Summary of the Invention

[0003] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0004] In view of the problems existing in the prior art, the inventors have proposed the present invention.

[0005] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method and application for preparing eutectic gels using a pretreated separation solution.

[0006] To solve the above technical problems, the present invention provides the following technical solution: a method for preparing eutectic gel using a pretreated separation liquid, comprising the following steps: (1) pretreating moso bamboo with urea / monoethanolamine alkaline eutectic solvent (ADES), collecting the separation liquid after solid-liquid separation, wherein the lignin content in the separation liquid is 1.06--5.25 mg / g and the hemicellulose content is 0.99--2.60 mg / g;

[0007] (2) The separation liquid obtained in step (1), acrylamide monomer, crosslinking agent N,N-methylenebisacrylamide (MBA), and initiator ammonium persulfate (APS) are mixed in a mass ratio of 4.6:0.69:0.00414:0.0069 and reacted at 85°C for 20-65 minutes to form a eutectic gel (DESgel);

[0008] (3) The eutectic gel obtained in step (2) is immersed in a 1-7 mol / L CuCl solution for 24 hours to complete the Cu 2 Adsorption, with an adsorption capacity of 20.71-29.34 mg / g.

[0009] As a preferred embodiment of the method for preparing eutectic gel using a pretreatment separation liquid according to the present invention, wherein: the ADES in step (1) is composed of urea and monoethanolamine in a molar ratio of 1:2, the pretreatment temperature is 40-120℃, the pretreatment time is 3 hours, and the solid-liquid ratio is 1:10.

[0010] As a preferred embodiment of the method for preparing eutectic gel using a pretreated separation liquid according to the present invention, wherein: the lignin content of the separation liquid in step (1) is controlled by the ADES pretreatment temperature: 1.06 mg / g at 40℃, 3.50 mg / g at 80℃, and 5.25 mg / g at 120℃.

[0011] As a preferred embodiment of the method for preparing eutectic gel using a pretreated separation solution according to the present invention, the reaction time in step (2) is extended with the increase of lignin content in the separation solution: 23 minutes when the lignin content is 1.06 mg / g, and 65 minutes when the lignin content is 5.25 mg / g.

[0012] As a preferred embodiment of the method for preparing eutectic gel using a pretreated separation solution according to the present invention, wherein: the concentration of CuCl solution in step (3) is 1 mol / L, and the conductivity of the eutectic gel after adsorption is increased to 0.099-0.403 S / m.

[0013] A method for preparing eutectic gels using a pretreated separation solution, wherein the components include:

[0014] Separation liquid of moso bamboo pretreated with urea / monoethanolamine alkaline eutectic solvent (ADES), wherein the lignin content is 1.06-5.25 mg / g and the hemicellulose content is 0.99-2.60 mg / g;

[0015] Polyacrylamide (PAM) network;

[0016] Copper ions (Cu) adsorbed on the gel network 2The adsorption capacity was 20.71-29.34 mg / g, and it was fixed to the phenolic hydroxyl groups and PAM amide groups of lignin by Cu-O / N coordination bonds.

[0017] As an application of the eutectic gel described in this invention in the fabrication of a flexible strain sensor, wherein: the resistance change rate ΔR / R of the sensor is linearly related to the strain in the strain range of 50%-400% (R 2 ≥0.998), sensitivity GF=2.1.

[0018] As an application of the eutectic gel described in this invention in the catalytic degradation of organic pollutants, the feature is that: the gel is placed in an organic pollutant solution containing HO, and a Fenton-like reaction is initiated through a Cu2 / HO system, with a degradation rate of ≥92% at 30℃.

[0019] A flexible strain sensor, wherein the eutectic gel is used as the sensing material.

[0020] As a preferred embodiment of the flexible strain sensor described in this invention, the resistance drift rate is <5% after operating at -20℃ for 24 hours.

[0021] The beneficial effects of this invention are as follows: By transforming the pretreated separation liquid into the core building blocks of a eutectic gel, this invention achieves a triple breakthrough gain. Through the synergistic utilization of lignin, hemicellulose, and residual solvents, a closed-loop system of "value-added from waste" is constructed, reducing raw material costs and mitigating environmental pollution risks. The molecular-level coupling of biomass components and the synthetic network creates a multifunctional synergistic effect: the rigid framework and π-π stacking of lignin endow the gel with exceptional environmental stability (resistance to dehydration and UV radiation), the dynamic hydrogen bond network of hemicellulose provides excellent toughness recovery, and the residual ADES components inhibit ice crystal growth through hydrogen bond recombination, allowing the material to remain flexible at -80℃. The precise construction of copper ions and lignin-Cu2 ​​coordination centers enables a single material to simultaneously possess both electron transport and catalytic activity. Furthermore, by exploring the intrinsic properties of biomass components, a novel pathway is provided for developing low-cost, environmentally adaptive smart materials. Detailed Implementation

[0022] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0023] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0024] Secondly, the term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single embodiment or an embodiment selectively excluded from other embodiments.

[0025] Example 1

[0026] This embodiment provides a method and application for preparing eutectic gels using a pretreated separation solution, specifically, the preparation of eutectic gels and the verification of flexible sensing performance.

[0027] Raw material pretreatment: Take 60-80 mesh bamboo powder and urea / MEA solvent (urea: monoethanolamine = 1:2 molar ratio) and mix at a solid-liquid ratio of 1:10. Stir and pretreat at 80℃ for 3 hours. Obtain the separated liquid by vacuum filtration (lignin content 3.50mg / g, hemicellulose content 2.60mg / g).

[0028] Construction of eutectic gel: The separation solution, acrylamide monomer, crosslinking agent MBA, and initiator APS were placed in a reactor at a mass ratio of 4.6:0.69:0.00414:0.0069. The reaction was carried out at a constant temperature of 85°C for 35 minutes to complete the preparation of eutectic gel (DESgel).

[0029] Metal ion functionalization (for sensing): The molded gel was immersed in 1 mol / L CuCl solution for 24 hours, and the adsorption capacity reached 27.15 mg / g.

[0030] Performance testing:

[0031] Electrical conductivity: The conductivity increased from 0.01 S / m to 0.124 S / m (Cu). 2 (To form a continuous conductive path).

[0032] Strain sensing performance: Within the tensile strain range of 50%-400%, the rate of change of resistance ΔR / R exhibits a highly linear relationship with strain: ΔR / R = 0.021ε + 0.003(R 2 =0.998), and the sensitivity (GF) is 2.1.

[0033] Mechanical properties: The compressive stress at 80% strain reaches 213.58 kPa (compared to unadsorbed Cu). 2 (Increase of 58%).

[0034] Furthermore, when the pretreatment temperature was adjusted to 40℃, the lignin content of the separation liquid decreased to 1.06 mg / g, at which point the gelation reaction time was shortened to 23 minutes, but Cu 2The adsorption capacity decreased to 20.71 mg / g, with limited improvement in conductivity (approximately 0.099 S / m). The adsorption capacity can be compensated for by increasing the CuCl concentration, but the conductivity may decrease (e.g., approximately 0.115 S / m at 3 mol / L).

[0035] Example 2

[0036] This embodiment provides a method and application for preparing eutectic gels using a pretreated separation solution, specifically, the application of eutectic gels in catalytic degradation.

[0037] Preparation of highly active gel: A separation solution (lignin 5.25 mg / g) was obtained by pretreatment at 120 °C. A eutectic gel was then prepared following the same steps as in Example 1 and subjected to Cu... 2 Adsorption (concentration increased to 29.34 mg / g, XPS confirmed an increased proportion of Cu-O / N coordination bonds).

[0038] Catalytic degradation operation and effect: 0.5g of Cu supported on... 2 The eutectic gel was placed in a solution containing 100 ppm methylene blue + 10 mM H2O and reacted by shaking at 30°C and 150 rpm.

[0039] Degradation is completed in 120 minutes, with a residual rate of ≤8.0% (degradation rate ≥92%).

[0040] The reaction follows first-order kinetics (k≈0.028 min). -1 ).

[0041] Specifically, lignin fixation of Cu2 forms active centers, initiating a Fenton-like reaction. Hemicellulose polyhydroxy chains enhance pollutant mass transfer (increasing BET surface area). The gel exhibits a degradation rate >85% after 5 reuses, attributed to network stability (such as the cellulose residue enhancement effect).

[0042] Example 3

[0043] This embodiment provides a method and application for preparing eutectic gels using a pretreated separation solution, specifically for the construction of a low-temperature stable strain sensor.

[0044] Fabrication of an antifreeze sensor: Based on the Cu-loaded sensor prepared in Example 1 2 Eutectic gels, after appropriate shaping (such as freeze-drying or direct cutting), are encapsulated with VHB tape to fabricate strain sensors. Structurally, this can be understood as follows: the core layer is Cu. 2 -PAM-lignin-hemicellulose conductive network (conductivity 0.124S / m), with an outer encapsulation for protection.

[0045] Extreme environment sensing performance test: After placing the sensor in an environment of -20°C for 24 hours, apply cyclic strain of 50%-400%. Record the resistance change using a digital multimeter.

[0046] Performance data:

[0047] 25℃ (control): Linearity R 2 =0.998, response deviation after 100 cycles <2%.

[0048] -20℃ (after 24 hours): Resistance drift ≤3.5%, linearity R 2 =0.992, deviation <5% after 100 cycles.

[0049] Specifically, the ADES residual components (urea / MEA) inhibit ice crystal growth through hydrogen bonding (DSC confirmed no glass transition at -80℃), and lignin provides ultraviolet shielding (UVB shielding rate of 97.27%), ensuring long-term stable operation of the sensor in outdoor or low-temperature environments (such as -30℃).

[0050] This invention achieves a closed-loop resource system for lignocellulosic biomass waste components by constructing a progressive technical route of "pretreatment-gelation-functionalization". Its core breakthrough lies in transforming the pretreatment separation liquid—a negative asset in traditional biomass refining—into a core raw material for high-performance materials. The gentle dissociation of bamboo by the urea / monoethanolamine alkaline eutectic solvent (ADES) not only efficiently releases cellulose (enzymatic hydrolysis yield >92%), but more importantly, precisely retains the active functional groups of lignin and hemicellulose in the separation liquid. Lignin, as the most abundant aromatic polymer in nature, plays a dual role in the gel network due to its densely packed phenolic hydroxyl and phenylpropane structures: on the one hand, it enhances the spatial stability of the three-dimensional network through the π-π stacking effect, significantly inhibiting water evaporation; on the other hand, it provides abundant metal coordination anchoring sites, enabling copper ions to be stably immobilized in a chemical coordination manner. This chemical immobilization mode fundamentally solves the defect of easy metal ion loss in traditional adsorption materials, laying the foundation for subsequent functional integration.

[0051] The direct gelation process of the separated liquid demonstrates the synergistic effect of all biomass components. In free radical polymerization, the phenolic hydroxyl groups of lignin competitively bind with acrylamide monomers, which, while prolonging the gelation time, enhances the network density through a rigid framework. Hemicellulose acts as a "flexible bridge"—its highly branched polyhydroxy chains form a dynamic hydrogen bond network with polyacrylamide (PAM), endowing the gel with excellent deformation recovery ability. Notably, the residual ADES component (urea / monoethanolamine) binds free water molecules through hydrogen bonding, allowing the gel to maintain flexibility at -80℃, completely solving the freeze-thaw failure problem of traditional hydrogels. This synergistic effect of components is particularly significant in mechanical properties: the rigid framework of lignin resists external stress, the dynamic cross-linking of hemicellulose buffers energy impacts, and the plasticizing effect of ADES enhances ductility, ultimately forming a strong and tough network with an elongation at break exceeding 260%.

[0052] The introduction of copper ions triggers a functional leap in the material. When copper ions are immobilized on the phenolic hydroxyl groups and PAM amide groups of lignin through coordination bonds, their effect far exceeds that of a simple additive—they reconstruct the electronic transport pathways and chemical reaction interfaces of the material. In the sensing dimension, the ionic conductivity pathway formed by copper ions couples with the electron delocalization of the aromatic rings of lignin: when the gel is stretched, the polymer chain orientation leads to the extension of the ionic pathway, while the microcracks generated by the rigid lignin framework increase the electron tunneling barrier. The synergistic effect of these two factors results in a highly linear response between resistance change and strain. This mechanism overcomes the limitations of traditional conductive gels that rely on a single conductivity mode, maintaining sensitivity stability, especially in the high strain range (>200%). In the catalytic dimension, Cu ions immobilized on lignin… 2 When combined with HO to form a heterogeneous Fenton-like system, its advantage lies in the fact that the lignin aromatic ring stabilizes the Cu / Cu2 redox cycle through electronic buffering, significantly extending the catalyst lifetime; while the hydrophilic microenvironment constructed by hemicellulose optimizes the generation and diffusion pathway of ·OH free radicals, enabling the pollutant degradation rate to exceed 92%.

[0053] The progressive design of the three embodiments verifies the universality and scalability of the technical route. Example 1, through the construction of the basic gel and the functionalization of copper ions, confirms the stable electro-mechanical coupling response of the material within a wide strain range (50%-400%). Example 2 further explores the catalytic potential of gels with high lignin content, revealing the regulatory mechanism of component content on reaction kinetics. Example 3, through extreme environment testing, highlights the antifreeze properties conferred by ADES residual components and the UV protection provided by lignin, ensuring the long-term stability of the device. The essence of this "dual-effect" characteristic (sensing and catalysis) stems from the multi-scale structural design of the material: at the molecular level, the lignin-Cu2 ​​coordination center serves as both an electron transport and catalytic active site; at the micro-nano scale, the hydrophilic channels constructed from hemicellulose simultaneously optimize electron transport and pollutant mass transfer efficiency; at the macroscopic scale, the core-shell structure reinforced by cellulose residue inhibits swelling and ensures functional stability.

[0054] From a circular economy perspective, this technology creates a green paradigm of "treating waste with waste." The complete resource utilization of the pretreated separation liquid avoids the chemical oxygen demand (COD) pollution caused by lignin / hemicellulose waste in traditional processes. The prepared gel sensor can monitor environmental pollutants in real time, and after its end-of-life, it can act as a Fenton-like catalyst to degrade organic wastewater, forming a closed loop of "monitoring-treatment." This strategy of transforming the limitations of biomass into functional advantages provides a new paradigm for green material design in a carbon-neutral context: no longer relying on precious metal modification or complex synthesis, but achieving the directional evolution of material properties through in-depth analysis of the interaction mechanisms of natural components.

[0055] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing eutectic gels using a pretreated separation solution, characterized in that: Includes the following steps: (1) The bamboo was pretreated with urea / monoethanolamine alkaline eutectic solvent (ADES), and the separated liquid was collected after solid-liquid separation. The lignin content in the separated liquid was 1.06-5.25 mg / g and the hemicellulose content was 0.99-2.60 mg / g. (2) The separation liquid obtained in step (1), acrylamide monomer, crosslinking agent N,N-methylenebisacrylamide (MBA), and initiator ammonium persulfate (APS) are mixed in a mass ratio of 4.6:0.69:0.00414:0.0069 and reacted at 85°C for 20-65 minutes to form a eutectic gel (DESgel); (3) The eutectic gel obtained in step (2) is immersed in a 1-7 mol / L CuCl solution for 24 hours to complete the Cu 2 Adsorption, with an adsorption capacity of 20.71-29.34 mg / g.

2. The method for preparing eutectic gel using a pretreated separation solution as described in claim 1, characterized in that: The ADES mentioned in step (1) consists of urea and monoethanolamine in a molar ratio of 1:2, with a pretreatment temperature of 40-120℃, a pretreatment time of 3 hours, and a solid-liquid ratio of 1:

10.

3. The method for preparing eutectic gel using a pretreated separation solution as described in claim 1, characterized in that: The lignin content of the separation liquid in step (1) is controlled by the ADES pretreatment temperature: 1.06 mg / g at 40℃, 3.50 mg / g at 80℃, and 5.25 mg / g at 120℃.

4. A method for preparing eutectic gel using a pretreated separation solution as described in any one of claims 1, characterized in that: The reaction time in step (2) increases with the increase of lignin content in the separation liquid: 23 minutes when the lignin content is 1.06 mg / g and 65 minutes when the lignin content is 5.25 mg / g.

5. The method for preparing eutectic gel using a pretreated separation solution as described in claim 1, characterized in that: In step (3), the concentration of CuCl solution is 1 mol / L, and the conductivity of the eutectic gel increases to 0.099-0.403 S / m after adsorption.

6. A eutectic gel prepared by a method for preparing a eutectic gel using a pretreatment separation solution as described in any one of claims 1-5, characterized in that: Its components include: Separation liquid of moso bamboo pretreated with urea / monoethanolamine alkaline eutectic solvent (ADES), wherein the lignin content is 1.06-5.25 mg / g and the hemicellulose content is 0.99-2.60 mg / g; Polyacrylamide (PAM) network; Copper ions (Cu) adsorbed on the gel network 2 The adsorption capacity was 20.71-29.34 mg / g, and it was fixed to the phenolic hydroxyl groups and PAM amide groups of lignin by Cu-O / N coordination bonds.

7. The application of the eutectic gel as described in claim 6 in the fabrication of flexible strain sensors, characterized in that: The resistance change rate ΔR / R of the sensor is linearly related to the strain within the strain range of 50% to 400% (R 2 ≥0.998), sensitivity GF=2.

1.

8. The application of the eutectic gel as described in claim 6 in the catalytic degradation of organic pollutants, characterized in that: The gel was placed in an organic pollutant solution containing HO, and a Fenton-like reaction was initiated through a Cu2 / HO system, with a degradation rate of ≥92% at 30°C.

9. A flexible strain sensor, characterized in that: The eutectic gel described in claim 6 is used as the sensing material.

10. A flexible strain sensor as described in claim 9, characterized in that: The resistance drift rate is <5% after operating at -20℃ for 24 hours.